Curriculum Transformation at Islamic Boarding High School: Moving Ahead Modernism - Mutiara Yolanda; Gunarhadi Gunarhadi; Agus Efendi (STAI Hubbulwathan Duri, 2025)
Education in Indonesia is evolving, including in Islamic boarding schools, which increasingly adopt modern approaches while preserving Islamic traditions. This study explores the curriculum movement at Modern Assalaam Islamic Boarding School, where national and boarding school curricula are integrated to balance modern education with traditional religious teachings. This study employs a qualitative case study approach, collecting data from eleventh-grade teachers through interviews, observations, and documentation. Data were analyzed using NVivo 14 software to encode, categorize, and identify emerging themes. Findings reveal that Assalaam Islamic Boarding School has successfully integrated technology, traditional boarding school practices, interactive learning, and collaboration with other educational institutions. Examples include using digital tools such as Canva, Excel, and PowerPoint in instruction, implementing practical sessions aligned with course content, utilizing the JOS program for material application, teaching practical skills like coding, and fostering cooperative learning through teacher-led group discussions. The institution demonstrates that curriculum transformation in Islamic boarding schools is essential to remain relevant and competitive. By incorporating technology and modern pedagogical strategies while preserving Islamic values, the school enhances student engagement and prepares them for contemporary challenges. Assalaam Islamic Boarding School serves as a model for integrating modernism and tradition in Islamic education. Its curriculum demonstrates adaptability to globalization and technological advancements while maintaining strong Islamic principles. Future research should explore curriculum adaptations in other Islamic boarding schools to enhance competitiveness in the modern era.